ABILITY OF NET INCOME, OPERATING CASH FLOW, AND SALES GROWTH IN PREDICTING FUTURE CASH FLOW - Atiya Karimanisa; Vicky Utami (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This research aims to examine the influence of net profit, operating cash flow, and sales growth in predicting a company's future cash flow. This is a quantitative research using secondary data from the financial reports of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sampling method used was purposive sampling, yielding a sample size of 105. The data analysis method employed in this research was multiple linear regression. The results of this research indicate that net profit has a positive influence on predicting a company's future cash flow, as evidenced by the statistical test results (t-test) showing a significant value supporting the hypothesis. Similarly, operating cash flow shows that it has a positive effect in predicting a company's future cash flow, as evidenced by the statistical test results (t-test) that support the hypothesis. In contrast to sales growth, which shows that sales growth does not affect predicting future cash flow, as evidenced by the statistical test results (t-test) showing that the significance value does not support the hypothesis.